Tourist police service quality and service culture influence on tourists' confidence/ Norfarah Nordin and Siti-Nabiha Abdul Khalid - Nordin, Norfarah; Abdul Khalid, Siti-Nabiha (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The travel and tourism sector is a significant economic contributor in Malaysia. Tourist police service quality plays an important role in promoting tourist confidence in the safety of a destination. However, there is less attention in tourism research focuses on tourist policing. Hence, this research fills the gap by examining the relationship between tourist police service quality and service culture influence on tourist confidence. The research is conducted in Penang Island, Malaysia. The dimension of tourist police service quality is conceptualized based on the SERVQUAL model with an additional factor - the service culture. The unit of analysis is international tourists. Based on the convenience sampling approach, a total of 150 completed responses was collected and analysed using the Partial Least Squares - Structural Equation Modelling (PLS-SEM) technique. This research finds that tourist confidence in the police is influenced by service quality factors: tangibles, responsiveness, and police service culture. The practical contribution of the research is on the utility of the finding for the Malaysian tourist police department to strategize their organization to achieve a better level of service quality, hence promotes tourist confidence.